State, justice and freedom. Contributions to political thought from Ditsö Káska and African diaspora - Schramm, Christina (2016)
In this article I discuss constructions of State, justice and freedom driving from interviews with native Bribri and Afro-descendent women in Costa Rica. I will argue in favor of Indigenous and Afro-descendent cultures as knowledge systems with own cosmologies and diasporic intellectual legacies that contribute significantly to the study of Political Thought. The intersection of interview quotations with those from other authors is, in this sense, thought as a political philosophical conversation. By this I respond to the urgent demand to decolonize academic knowledge production on the one side, and to strengthen anti-discriminatory policies on the other. In this article I continue discussing some of the main results of my Spanish written doctoral thesis “From this other side…”: Subjectivities and social imaginaries of Afro-descendent and native Bribri women in Costa Rica (Schramm, 2013).